WRITING STYLE COMPARISON BETWEEN MALE AND FEMALE STUDENTS IN WRITING ARGUMENTATIVE ESSAY - Amalia Salsabila; Atti Herawati; Istiqlaliah Nurul Hidayati (Journal of English Teaching and Linguistics Studies (JET Li), 2021)
Male and female students have different and similar writing styles. These differences and similarities make them have their own characteristics in writing. The differences that occur can be seen in terms of lexical and grammatical features. This research aimed to compare writing style between male and female students in writing argumentative essay. This research was conducted at English Language Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. There were four male and four female students from 4A in this research as the participants. To gain the research data, the researcher used three research instruments: documentation, questionnaire, and interview. Documentation instrument was used to analyze students’ work. Questionnaire instrument was distributed two times for each student. Interview was conducted once for each student. According to the data analysis, it was found that there are two similarities and three differences between male and female students in writing argumentative essay. The similarities are the use of psychological processes and the use of sentence structure, punctuation, and capitalization. The differences are the way to express the opinion, the use of words, and the use of certain possessive pronouns more frequently